The association between serum complement C3a and severity in patients with community-acquired pneumonia - Xu, Zheng; Hou, Xue-Feng; Feng, Chun-Mei; Zheng, Ling; Xu, De-Xiang; Zhao, Hui; Fu, Lin (Frontiers in Immunology, 2023)
Background: A few studies found that complement system may involve in the onset and progression of community-acquired pneumonia (CAP). However, the role of complement system in CAP was obscure. The goal of this study was to analyze the association of serum complement C3a with CAP severity scores based on a cross-sectional study. Methods: All 190 CAP patients and 95 control subjects were enrolled. Demographic information and clinical data were extracted. Peripheral blood samples were collected on admission. Results: Serum complement C3a on admission were elevated in CAP patients compared with control subjects. The level of complement C3a was gradually elevated parallelly with CAP severity scores (CURB-65, CRB-65, PSI, SMART-COP and CURXO). Complement C3a was significantly and positively correlated with blood routine parameters, renal function markers and inflammatory cytokines in CAP patients. Furthermore, mixed linear and logistic regression models found that serum complement C3a on admission was positively associated with CAP severity scores. Mechanism research suggested that complement system inhibition alleviated streptococcus pneumoniae-induced the upregulation of IL-1β, TNF-α, IL-6 and CRP expressions in MLE-12 cells. Conclusions: Serum complement C3a on admission is positively associated with the severity of CAP patients. Inhibiting complement system attenuates streptococcus pneumoniae exposure-elevated the secretion of inflammatory cytokines in pulmonary epithelial cells, indicating that complement C3a is involved in the pathophysiology of CAP. Serum complement C3a may be served as an earlier diagnostic biomarker for CAP.